Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

A gender analysis of the impact of indirect taxes on small and medium enterprises in Vietnam - Akram-Lodhi, A Haroon; van Staveren, Irene (Institute of Social Studies, 2003)
This paper brings together gender analysis, small scale enterprise analysis, and gender budget analysis in a development context. The paper demonstrates that gender matters not only to the ownership of an SME, but also to its most likely principal activity, the stock of the assets that it possesses, the labour that it utilizes, the costs that it faces, the revenues that it generates, and the profits that it earns. In particular, lower earnings for female-owned SMEs can be attributed to the different input cost structures facing female and male-owned SMEs, which in turn are influenced by the indirect tax system. In this context, the paper identifies five gender biases in Vietnam’s VAT system. These biases help explain the higher costs and lower profits of female-owned SMEs in Vietnam. This explanation is different from the more common explanation given for lower performance of female owned enterprises in developing countries, which is the gender segregation of sectors. Although this also plays a role, we argue that gender biases in costs and earnings, partly caused by the tax system, are the more dominant factor.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; gender / género

Deviations between the Planned and the Execution Undermine the Health Budget – Observatório do Cidadão para Saúde - Observatório Cidadão para Saúde
In Mozambique, health services are mostly provided by the public sector, and it is the responsibility of the Ministry of Health (MISAU) to enable the creation, planning and control of national health policies. The health sector is the third sector that absorbs most resources from the State Budget (OE), followed by the Education and Infrastructure sectors, according to the methodology presented in the budget documents related to the economic and social sectors. This sector is divided into three levels: namely, the Central Level, which is represented by MISAU; The Provincial Level, which is represented by the Provincial Health Directorates (DPS); and Finally, we have the District Level, which is represented by the Health, Women and Social Action Secretariats (SDSMAS). Therefore, it will be based on these levels that our analysis of allocations to the health sector in the period from 2015 to 2020 will be undertaken.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; health - health services / serviços de saúde